PENGARUH KEPEMIMPINAN KENABIAN DAN SPIRITUALITAS DI TEMPAT KERJA TERHADAP PERILAKU EKSTRA PERAN (ORGANIZATIONAL CITIZENSHIP BEHAVIOR) DALAM PERSPEKTIF ISLAM (Studi pada Sinergi Foundation) - Allya Roosallyn Assyofa (Jurnal Manajemen Bisnis Performa, 2016)
The purpose of this study is to investigate phenomenon about organizational citizenship behavior from Islamic perspective. This study is important because of the fact that research about prophetic leadership, workplace spirituality and organizational citizenship behavior emanating from the Western value system and gives insufficient consideration to the Islamic perspective. This study analyses the direct effect from prophetic leadership to OCB, the direct effect from workplace spirituality to OCB and both effect simustaneosly in the context of Zakah Institution (LAZ) with research subject are Sinergi Foundation employees. This study uses descriptive analysis with verificative method to experiment the influence between variables. Observation, interview and questionaire was used to collects data. Using path analysis this research results is there are positive influence from prophetic leadership and workplace spirituality to OCB both partially and simultaneously.